Modern India and the Tale of Twin Nutrient Deficiency–Calcium and Vitamin D–Nutrition Trend Data 50 Years-Retrospect, Introspect, and Prospect - Harinarayan, Chittari Venkata; Akhila, Harinarayan (Frontiers in Endocrinology, 2019)
Vitamin D and calcium are essential nutrients for bone health, to achieve peak bone mass and to preserve bone, as age advances. The deficiency of this twin nutrient casts long shadows in later life as short/long latency diseases–rickets/osteomalacia/osteoporosis. There is scant review available about the trend of these nutrients in India. For over past half a century, the intake of dietary calcium, milk, milk products and cereals has declined drastically in the background of upward revision of RDA/RDI in modern India. This is attributed to changing lifestyle, inadequate milk consumption across various socio-economic strata, and shift in dietary intake from cereals to rice and wheat. There is a clear rural–urban divide in consumption of milk, milk products and cereals, a change in dietary habits which magnify the calcium and vitamin D deficiency. Revisiting of RDA guidelines for calcium along with public health measures is required to tackle the morbidity arising due to twin nutrient deficiency. Any measure to addresses this issue in isolation, without achieving the desired benefits, is a disservice to the population. Population based educational strategies, government measures, leveraging technology, adequate sun exposure and food fortification help tackling the twin nutrient deficiencies in this diverse country.